Redefining 'Propaganda': The Media Strategy of the Islamic State. Issue 1 (2nd January 2020) - Winter, Charlie
Abstract : This work was supported by a research award from Facebook as part of its 'Content Policy Research on Social Media Platforms' research project. The views and conclusions contained in this document are those of the author and should not be interpreted as representing the policies, either expressed or implied, of Facebook. In this article, Charlie Winter challenges the way in which the word 'propaganda' is used in contemporary discourse around war and terrorism. He considers the case of the Islamic State, using it to demonstrate that the term – as it is conventionally understood – is an inadequate tool when it comes to describing the full range of tactical and strategic approaches to communication that are employed by insurgents today. If anything, he contends, 'propaganda' refers to an entire information ecosystem in which different media are geared towards different tasks.